CLINICAL EDUCATION DURING COVID-19 PANDEMIC: EXPLORING MEDICAL STUDENTS AND CLINICAL SUPERVISORS’ EXPERIENCES - Noija, Stazia; Suhoyo, Yoyo; Hidayah, Rachmadya Nur (Universitas Gadjah Mada, 2023)
Background: COVID-19 has become a global pandemic that has caused significant changes, including in the context of implementing clinical education. Medical students and clinical supervisors face various adjustments that become a dilemma. This study aims to explore the implementation of clinical education in the era of the COVID-19 pandemic based on the experiences of medical students and clinical supervisors.Methods: Qualitative research was performed using purposive sampling. Informant interviews were arranged until data saturation was achieved, followed by an analysis process using thematic analysis.Results: Seven themes were identified, including learning opportunities and engagement, interaction with patients, communication and interaction with colleagues and supervisors, facility and individual management, supervision process, awareness and confidence, and evaluation and assessment on clinical rotation. The results of this study indicate several changes in the implementation of clinical education during the COVID-19 pandemic compared to before the COVID-19 pandemic.Conclusion: There are several noticeable changes in the implementation of clinical education during the COVID-19 pandemic compared to before the pandemic by referring to the experiences of medical students and clinical supervisors. It is related to the factors that influence the implementation of clinical education during the COVID-19 pandemic.